МODIFIED CROSS-LINKING IN THE TRЕATMENT OF ADVANCED PURULENT CORNEAL ULCER. СLINICAL CASE - Evg. A. Kasparova; Ian Byao; O. I. Sobkova (Oftalʹmologiâ)
Purpose: To describe the clinical case of advanced purulent corneal ulcer successfully treated with modified cross-linking (M-CXL). Key points: A developed purulent corneal ulcer augmenting from the center to the limb with stromal lysis in the zone of keratotomy incisions gradually progressed despite active conservative treatment during 1 month. After 2 sessions of modified PACK-CXL performed with simultaneous frequent instillations of preservant-free moxifloxacin eye drops, the purulent process and corneal lysis was successfully stopped. It allowed to perform optical penetrating keratoplasty in the non-inflamed eye and use smaller graft diameter. Conclusion: M-CRL demonstrated an excellent therapeutic effect — rapid resorption of active purulent infiltration and suppression of purulent corneal melting. This allowed to avoid emergency keratoplasty and to conduct it as a planned operation. M-CXL can become a promising method of treating purulent corneal ulcers in the absence of the effect of drug therapy, and also be used as a preparation for keratoplasty surgery to reduce the severity of inflammation and the risk of infection recurrence in the postoperative period.